Analisis Isi Kebijakan Perbandingan Peraturan Daerah Pengelolaan Sampah di Jawa Tengah Tahun 2017-2021 - Aprilia Anggi Permatasari; Rutiana Dwi Wahyunengseh (Jurnal Mahasiswa Wacana Publik, 2022)
This study aims to identify the main points regulated in local regulations in each district/city in Central Java, and to find out the similarities and differences between each regulation. According to Grindle, the success of a policy can be seen from the content of the policy itself. The method used in this research is a mixed research method, namely qualitative with secondary data analysis approach and descriptive quantitative. The source of data comes from secondary data, namely in the form of archives of regional regulations. Data collection techniques are carried out through archival documentation. Researchers will analyze regional regulations using a content analysis approach. The results showed that the points regulated in the local regulations for waste management in several districts/cities in Central Java have similarities and differences. Of the 7 aspects analyzed, only the Site of decision aspects are the same from one regional regulation to another. The decision-making positions in the form of district/city regulations are the same, namely the Regency/City DPRD and the Regent/Mayor. All regional regulations have met the indicators in Presidential Regulation No. 59 of 2017. The waste management methods used in all regional regulations apply the 3R concept, namely reduce, reuse, and recycle. The 3Rs have entered into the circular economy concept but have not fully implemented the circular economy concept. Basically the circular economy concept is waste managed with 5R (reduce, reuse, recycle, recovery, and repair).